2013
DOI: 10.1074/jbc.m113.483305
|View full text |Cite
|
Sign up to set email alerts
|

Two-sided Ubiquitin Binding of NF-κB Essential Modulator (NEMO) Zinc Finger Unveiled by a Mutation Associated with Anhidrotic Ectodermal Dysplasia with Immunodeficiency Syndrome

Abstract: Background: Mutations in the NEMO ZF cause various forms of anhidrotic ectodermal dysplasia with immunodeficiency (EDA-ID). Results:The NEMO ZF contains a larger ubiquitin binding surface, which is required for IKK/NF-B activation. Conclusion:This study provides an understanding of how defective mutations of NEMO ZF in NF-B signaling leads to the EDA-ID pathology. Significance: This study provides novel insights in the NEMO ZF-dependent mechanisms for IKK activation in NF-B signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Most recently, Ngadjeua et al have modeled the NEMO ZF with Lys-63-linked di-ubiquitin, through extensive mutational and genetic complementation studies. Interestingly, in their analysis they implicated Phe-395 as a critical reside for interacting with the Ile-44 patch of the proximal Lys-63-linked di-ubiquitin (19). We observed that swapping Phe-395 and Cys-396 to generate Cys-395/Phe-396 nearly abolished all WA-induced increased polyubiquitin chain binding (Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Most recently, Ngadjeua et al have modeled the NEMO ZF with Lys-63-linked di-ubiquitin, through extensive mutational and genetic complementation studies. Interestingly, in their analysis they implicated Phe-395 as a critical reside for interacting with the Ile-44 patch of the proximal Lys-63-linked di-ubiquitin (19). We observed that swapping Phe-395 and Cys-396 to generate Cys-395/Phe-396 nearly abolished all WA-induced increased polyubiquitin chain binding (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Abolishing the ubiquitin binding function of the UBAN domain via point mutations has been shown to severely attenuate NF-B activation (14, 16 -18). The other UBD in NEMO is the C-terminal ZF domain, which has M1-and Lys-63-linked polyubiquitin chain binding capabilities as well as a proposed model of this interaction (19). While the ZF domain is not generally necessary for NF-B activation by canonical inducers (20), it does appear to be required for a full signaling response to TNF␣, IL-1␤, and bacterial lipopolysaccharide (LPS) (21).…”
mentioning
confidence: 99%
“…BCL10 is modified by both K63-polyubiquitin and linear polyubiquitination in ABC DLBCL, and both modifications depend on cIAP1/2. The recruitment of IKK NEMO depends on its UBAN ubiquitin-binding domain, which binds both K63- and linear polyubiquitin chains with different relative affinities (Kensche et al, 2012; Ngadjeua et al, 2013). Conceivably, the initial recruitment of IKK to the CBM complex may depend on its interaction with K63-ubiquitinated BCL10, while IKK retention in the CBM complex may be fostered by linear ubiquitination of BCL10 subsequent to LUBAC recruitment to the CBM complex.…”
Section: Discussionmentioning
confidence: 99%
“…The L322P mutation is within the leucine zipper region and prevents the recognition of both linear and K63-linked di-ubiquitin (Wu et al, 2006). Finally, the C-terminal ZF domain, which preferentially recognizes K63-linked ubiquitin polymers, is inactivated by the V407S mutant (Cordier et al, 2009;Laplantine et al, 2009;Ngadjeua et al, 2013). Thus, each of these mutants impaired the reconstitution of NFκB activation in a NEMO-deficient reporter cell line: the Y301S and L322P mutants were profoundly inactive, the R312Q mutant was impaired and the V407S mutant showed an intermediate defect ( Fig.…”
Section: Poly-ubiquitin Binding Sites Promote Assembly Of Nemo Into Smentioning
confidence: 99%
“…The helical region is linked to an unstructured linker and a C-terminal zinc finger (ZF) domain. The NEMO ZF domain also binds pUb, but prefers K63-linked polymers (Cordier et al, 2009;Laplantine et al, 2009;Ngadjeua et al, 2013). Mutations that impair the interactions of NEMO with the IKK kinases, linear pUb chains, or K63-linked pUb chains are among the most common causes of NEMOassociated immune dysfunction (Hanson et al, 2008;Senegas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%